Vaccine hesitancy in families of children during the COVID-19 pandemic - Izabella da Silva Viana; Emília Gallindo Cursino; Liliane Faria da Silva; Maria Estela Diniz Machado; Elenice Maria Cecchetti Vaz (Universidade Federal do Ceará, 2023)
Objective: to identify the reasons that led families of children to vaccine hesitancy during the COVID-19 pandemic. Methods: qualitative study with semi-structured interviews carried out with 20 children's relatives, all of which were mothers of hospitalized children. Data was submitted to lexicographical analysis in the software Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires, using descending hierarchical classification. Results: the fear of leaving one's house during the pandemic and the lack of vaccine supplies were the reasons found for vaccine hesitancy in the family of children during the COVID-19 pandemic. Conclusion: the reasons for vaccine hesitancy in the families of children found in this study threaten advancements in the struggle against vaccine-preventable diseases. Contributions to the practice: government bodies, managers, and health unit nurses should be co-responsible for efficient measures to implement health education in this public, creating a bond of trust to reduce the risks from the increase in vaccine hesitancy and reduction in vaccine coverage in the country.